2010
DOI: 10.1121/1.3290175
|View full text |Cite
|
Sign up to set email alerts
|

Structural damage identification in plates via nonlinear structural intensity maps

Abstract: A nonlinear structural intensity concept is presented as an approach for the identification of defects displaying nonlinear vibration behavior. The nonlinear structural dynamic response exhibited by a riveted joint with loosened fasteners connecting a stiffener with a flat panel is investigated. The excitation, generating elastic waves with dominant bending components, triggers the nonlinear contact between the plate and the stiffener inducing a dynamic response rich with nonlinear harmonics. Experimental stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…13 Donskoy et al utilized a modulated wave interrogation technique to implement a nondestructive evaluation system, capable of analyzing more complex structures. 14 Recent work by Conlon and Semperlotti et al [15][16][17] showed the use of SI and nonlinear structural intensity (NSI) as health monitoring techniques for rotorcraft airframe structures by exploiting the nonlinear behavior of CAN. Linear SI relies on determining the energy flow present in a structure from only the driving (source) frequencies.…”
Section: B Intensity Based Shm Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Donskoy et al utilized a modulated wave interrogation technique to implement a nondestructive evaluation system, capable of analyzing more complex structures. 14 Recent work by Conlon and Semperlotti et al [15][16][17] showed the use of SI and nonlinear structural intensity (NSI) as health monitoring techniques for rotorcraft airframe structures by exploiting the nonlinear behavior of CAN. Linear SI relies on determining the energy flow present in a structure from only the driving (source) frequencies.…”
Section: B Intensity Based Shm Overviewmentioning
confidence: 99%
“…These singlesensor metrics, denoted nonlinear strain (NLS) and nonlinear acceleration (NLA), are applied in a similar manner to NSSI and NSSI-MW in the frequency domain [see Eqs. (15), (16), (19), and (20)]. Each metric is developed using the respective sensor autospectra (strain or acceleration) and sums the content in the band around the prescribed nonlinear harmonics.…”
Section: B Implementation Of Experimental Techniquesmentioning
confidence: 99%
“…The latter approach proposed in the literature has been named as the second harmonic imaging technique. Higher harmonic components were also considered in the context of structural integrity maps used for damage localization . More recently, an enhancement of the higher harmonics mapping technique—based on the concept of the local defect resonance (LDR)—has been proposed.…”
Section: Nonlinear Acoustics For Damage Detection and Localizationmentioning
confidence: 99%
“…In turn, the spatial derivatives of the out-of-plane displacement fields provide the necessary inputs for the assessment of SI and the localization of sources and sinks. Many studies have already been carried out to estimate the energy flow in the form of vector fields or by calculating its divergence, which allows clear visualization of vector's dispersion or convergence [4,5,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%